Analysis of Existing Approaches to Mapping Environmental Pollution - Manoev, Sanat Bakhronovich; Azzamov , Giyos Xudaynazarovich (Researchparks Publishing, 2023)
According to N.F. Reimers (1990), pollution is understood as the introduction into the environment or the emergence in it of new, usually uncharacteristic for it, physical, chemical, biological, informational agents or the excess of the natural long-term average concentration level at the considered time, leading to negative consequences. With such a broad interpretation of the concept of pollution, its traditional division into chemical, physical and biological becomes insufficient and is supplemented by geological and geomorphological.